The Effect of Debt to Asset Ratio (DAR) and Total Assets Turnover (TATO) on Financial Distress Conditions at PT Gajah Tunggal Tbk. - Budhiarjo, Intan Sari (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to ascertain how PT Gajah Tunggal Tbk's financial distress conditions are impacted by the debt to asset ratio (DAR) and total assets turnover (TATO). The research methodology employed in this study is quantitative descriptive, meaning that the issues the organization faces are discussed together with a financial situational analysis given in numerical form. The financial ratios under investigation include the activity ratio, which is proxied by total asset turnover (TATO), and the solvency ratio, which is proxied by debt to asset ratio (DAR). Secondary data from PT Gajah Tunggal Tbk's income statement and balance sheet was utilized. time frame acquired from the Indonesia Stock Exchange (IDX). The partial calculation of the analysis's data indicates that the Debt to Asset Ratio (DAR) has a substantial negative effect on financial hardship, with a significance value of 0.021 < 0.05 and a ttable (-2.974 > -2.365). Financial hardship is significantly positively influenced by Total Assets Turnover (TATO) when fcalculate > ttable (3,229 > 2.365) with a significance value (0.014 < 0.05). Then, based on the test coefficient of determination (R Square) of 0.905, analyze concurrently Fcalculate > Ftable (33.295 > 4.74) with a significance value (0.000 > 0.05), indicating that there is a simultaneous significant effect between Debt to Asset Ratio (DAR) and Total Assets Turnover (TATO) on financial distress. This result indicates a 90% percentage, with other factors influencing the remaining 10%.